2017
DOI: 10.1292/jvms.16-0300
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an HPLC assay for determination of Telazol in pregnant pigs: application to placental transfer study

Abstract: Anesthetics utilized for the immobilization of pregnant mammals are prone to crossing the placental barrier and cause adverse effects to the fetuses. In this study, we develop a facile method employing high performance liquid chromatography (HPLC) for the study of Telazol crossing the placental barrier of pregnant pigs. The method mainly relies on the efficient extraction strategy that includes the mobile phase composed of 10 mM ammonium acetate aqueous solution-acetonitrile (1:4, v/v). When the injected dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
(16 reference statements)
1
0
0
Order By: Relevance
“…However, the findings of the current study did not appear to have this difference in t ½ (zolazepam 1.2 h versus tiletamine 1.5 h) after administration IM. Our findings may be a result of the combination of drugs that were similar to those found in a study of pregnant pigs [ 41 ], where the C max for both tiletamine and zolazepam was 50–60 min (compared to 10–12 min in the present study), and where the elimination of zolazepam was slow and tiletamine rapid. The study also showed that zolazepam, but not tiletamine, was detected in the uterus and umbilical cord and thereby probably having an effect on the fetus; this finding must be taken into consideration when used in pregnant sows.…”
Section: Discussionsupporting
confidence: 90%
“…However, the findings of the current study did not appear to have this difference in t ½ (zolazepam 1.2 h versus tiletamine 1.5 h) after administration IM. Our findings may be a result of the combination of drugs that were similar to those found in a study of pregnant pigs [ 41 ], where the C max for both tiletamine and zolazepam was 50–60 min (compared to 10–12 min in the present study), and where the elimination of zolazepam was slow and tiletamine rapid. The study also showed that zolazepam, but not tiletamine, was detected in the uterus and umbilical cord and thereby probably having an effect on the fetus; this finding must be taken into consideration when used in pregnant sows.…”
Section: Discussionsupporting
confidence: 90%